On Rational Amoralists - Zavaliy, Andrei (2012)
An influential tradition in moral philosophy attempts to explain an immoral action by reference to the defect in reasoning on the part of an immoral agent. On this view, the requirements of morality are not only sanctioned by the more general requirements of rationality, but the violations of the moral requirements would be indicative of a rational failure. In this article I argue that ascription of irrationality to amoral individuals (e.g., psychopaths) is either empirically false, or else, conceptually problematic. An interpretation of irrationality in its instrumental sense fails to do justice to the results of the research concerning the intelligence of some amoralists, whereas the suggestion that the alleged cognitive deficiency lies at the level of final ends and ultimate values faces serious theoretical difficulties. All attempts to construe the notion of an external reason for action without reference to the agent's actual goals and values bespeak an objectivist's bias, rest on controversial assumptions, and tend to alienate the agent from the proposed set of reasons. The argument is partly based on the analysis of reasoning of Ted Bundy, a notorious serial murderer, who presents a rather sophisticated justification for his criminal behavior.